Correlation between sizes and intracystic pressures of hydatid cysts - BATIREL, HASAN FEVZİ (My University, 1997)
BACKGROUND: A bicentral prospective study was performed to assess the relationship between sizes and intracystic pressures (ICP) of pulmonary hydatid cysts as well as to compare these measurements in different age groups. METHODS: A total of 20 patients with 22 unperforated pulmonary hydatid cysts underwent surgery between April 1994 and September 1995. There were 12 males and 8 females with a mean age of 25.7 (7-62). Intraoperatively, ICP's were measured in cmH2O by direct cannulation. RESULTS: Out of a total of 22 cysts, 12 were located in the lower lobes. Mean diameter, volume and ICP of cysts were 9.6 cm (S.D. 4.2), 728.8 cm3 (S.D. 1014.9) and 36.6 cmH2O (S.D. 9.3), respectively. There was no significant correlation between various measurements of hydatid cysts, namely their short and long diameters, volumes and intracystic pressures (P > 0.05). There was no difference regarding the volume, ICP and age of patients, either among pulmonary lobes or between sexes. Patients who were 20 years old and less, presented a mean cystic diameter of 7.2 cm and mean ICP of 35.1 cmH2O, whereas the over 20 age group showed results of 11.9 cm and 38.1 cmH2O, respectively (P values were < 0.0083 for diameter and > 0.05 for ICP). CONCLUSIONS: Due to the small sample size and a few extreme measurements, the correlation between the sizes and the pressures of hydatid cysts turned out to be insignificant, but it is believed that a positive correlation is most probable with larger sample sizes. On the other hand, while the difference between the mean cystic diameters in age groups of below and over 20 was significant, the pressure difference between them was insignificant. This is why young patients carry the same risk of perforation as adults, although they present with relatively smaller cysts. Therefore, due to the well-known anaphylactic, obstructive and infectious risks of hydatid cyst perforation, urgent surgical removal is always necessary.
Keywords: Adult; Female; Humans; Middle Aged; Prognosis; Aged; Adolescent; Male; Child; Retrospective Studies; Pressure; Monitoring, Intraoperative; Rupture, Spontaneous; Manometry; Echinococcosis, Pulmonary